THE EFFECT OF JOB TRAINING AND JOB MOTIVATION ON TEACHER PERFORMANCE THROUGH JOB SATISFACTION AT SMK NEGERI 9 MEDAN - Muhammad Arief Wijaya; Muhammad Alfahmi (International Journal of Management, Economic and Accounting, 2025)
Through job satisfaction at SMK Negeri 9 Medan, this study seeks to investigate how work motivation and training affect teacher performance. Teacher performance, which is impacted by a number of factors such as job motivation, job satisfaction, and training received, is a significant component in raising the quality of education. This study employs a survey method in conjunction with a quantitative approach. Eighty teachers at SMK Negeri 9 Medan were given questionnaires to complete in order to gather data, which was then processed using the Smart PLS application. The study's findings demonstrate that job training significantly and favorably affects teachers' job happiness, which in turn improves their performance. Furthermore, it has been demonstrated that work motivation influences teacher performance both directly and indirectly through job satisfaction. This study advances knowledge about the significance of maintaining work motivation and developing competencies through training in enhancing teacher performance at SMK Negeri 9 Medan. In order to enhance teacher performance and job happiness, schools are advised to keep creating suitable training programs and fostering a positive work atmosphere.